(untitled) (Memoria Americana. Cuadernos de Etnohistoria, 2013)
Reseña sobre el libro escrito por Gary Van Valen (2013) titulado Indigenous agency in the Amazon: The Mojos in liberal and rubber-boom Bolivia, 1842-1932. Tucson, The University of Arizona Press.